Adhesive micro-line periodicity determines guidance of axonal outgrowth() - Hart, Steven R. (2013)
Adhesive micro-lines of various sub-cellular geometries were created using a non-traditional micro stamping technique. This technique employed the use of commercially available diffraction gratings as the molds for the micro stamps, a method which is quick and inexpensive, and which could easily be adopted as a patterning tool in a variety of research efforts. The atypical saw-tooth profile of the micro stamps enabled a unique degree of control and flexibility over patterned line and gap widths. Cortical neurons cultured on patterned poly-lysine micro-lines on PDMS exhibit a startling transition in axonal guidance: From the expected parallel guidance to an unexpected perpendicular guidance that becomes dominant as patterned lines and gaps become sufficiently narrow. This transition is most obvious when the lines are narrow relative to gaps, while the periodicity of the pattern is reduced. Axons growing perpendicular to micro-lines exhibited ‘vinculated’ growth, a unique morphological phenotype consisting of periodic orthogonal extensions along the axon.